2010
DOI: 10.1093/heapol/czq066
|View full text |Cite
|
Sign up to set email alerts
|

An offer you can't refuse? Provider-initiated HIV testing in antenatal clinics in rural Malawi

Abstract: International organizations promote provider-initiated, 'routine' HIV testing of pregnant women seeking antenatal care as an effort to curb mother-to-child transmission. We offer an account of the perceptions of HIV testing at antenatal clinics in rural Malawi. Although it is both international and Government of Malawi policy that women must be explicitly informed of their right to refuse testing, analysis of in-depth interviews, focus group discussions and evidence from observational field journals show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 20 publications
(24 reference statements)
1
79
0
Order By: Relevance
“…Fear of stigma fuels a fear of HIV testing, which keeps women from presenting to clinics. Despite the current system of provider-initiated testing, many women are still unaware of their right to decline testing, as reported in other Sub-Saharan countries [21]. A myriad of sociocultural factors, compounded by local realities of care delivery, prevent women from making demands regarding their health care and further delay decisions to seek care.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of stigma fuels a fear of HIV testing, which keeps women from presenting to clinics. Despite the current system of provider-initiated testing, many women are still unaware of their right to decline testing, as reported in other Sub-Saharan countries [21]. A myriad of sociocultural factors, compounded by local realities of care delivery, prevent women from making demands regarding their health care and further delay decisions to seek care.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that reported on the acceptability of PITC included only small samples of women and did not involve interviews with women who declined an offer of HTC. 28,31,32 In addition, the studies included in our review are subject to their own limitations: the majority were nonrandomized studies and the difficulty of reporting and synthesizing evidence from nonrandomized studies is well documented. 39 Moreover, studies were subject to acquiescence bias 40 and, as the questions posed to patients were different in each study, it was difficult to compare their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Women who had been tested for HIV during their most recent pregnancy (i) 52% believed they had clearly consented to testing and had a positive experience of group and individual education sessions; (ii) 28% said their choice was "less clear" and were less positive about the education sessions; (iii) 20% felt their choice had been compromised (48% of these women expressed the view that they experienced less autonomy in deciding whether to be tested for HIV) Angotti, 2010 28 …”
mentioning
confidence: 99%
“…In Malawi, researchers examined perceptions of HIV testing during pregnancy and reported that despite an official policy indicating that women must be informed of their right to refuse to test, "rural Malawians [did] not perceive HIV testing as a choice, but rather as compulsory in order to receive antenatal care" (Angotti et al, 2011, p. 307). Participants in Amuru also perceived couples' testing during ANC to be "an offer you can't refuse" (Angotti et al, 2011). Angotti et al's (2011) study, which focused on Malawi women's (and not couples') testing, identified a "dissonance between global expectations and local realities of the delivery of HIV-testing interventions" (p. 307).…”
Section: The Power To Enforce Normative Relationship Standardsmentioning
confidence: 99%